2020
DOI: 10.18006/2020.8(spl-1-sars-cov-2).s210.s218
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Vaccine Acceptance: Beliefs and Barriers Associated With Vaccination Among the General Population in India

Abstract: Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a novel zoonotic coronavirus that emerged from Wuhan, China. Development of SARS-CoV-2 specific vaccine is considered as the only solution that could control this pandemic. However, the success of COVID-19 vaccination programme will be dependent on the development of effective and safer vaccines and also on the public acceptance which in turn reliant on the beliefs and perception towards the vaccine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
77
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(106 citation statements)
references
References 0 publications
12
77
3
Order By: Relevance
“…Sharun et al reported that in a similar study, via a selfadminister questionnaire online, nearly 85% of the 351 subjects were planning to get the COVID-19 vaccine once it is available for use in the market. 4 Less than two thirds of their subjects, however, were ready to get the vaccine as soon as it was available, and the most important cause of vaccine hesitancy was the fear of side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sharun et al reported that in a similar study, via a selfadminister questionnaire online, nearly 85% of the 351 subjects were planning to get the COVID-19 vaccine once it is available for use in the market. 4 Less than two thirds of their subjects, however, were ready to get the vaccine as soon as it was available, and the most important cause of vaccine hesitancy was the fear of side effects.…”
Section: Discussionmentioning
confidence: 99%
“…5 Most cross-sectional surveys across the globe have revealed similar responses amongst the study subjects. [3][4][5][6][7][8][9][10] More than two-thirds of the study participants in the USA were willing to get COVID-19 vaccine. 6 On the other hand, in China, the COVID-19 vaccine acceptability rate was found to be more than 90%.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, executed before the COVID-19 vaccination program (when the spread was intensive with alarming number of cases, registered per day) had started in India, varied acceptance levels of 86.3 % (Sharun et al 2020), 77.3 % (Gautam et al 2020, 74.5 % (Lazarus et al 2021) and 74 % (Kazi Abdul and Khandaker Mursheda, 2020) were recorded. Similarly, a high acceptance was observed in others countries like US (80 %) (Thunstrom et al 2020), and China (72.5 %) (Fu et al 2020) prior to vaccination.…”
Section: Assessment Of Vaccine Acceptancementioning
confidence: 99%
“…Therefore, the objective of this pan-India online survey was to assess our citizens' awareness and acceptance of the current COVID-19 vaccination program. Although a couple of previous surveys were directed towards assessing the acceptance of the COVID-19 vaccine prior to the launch and use of the vaccine (Sharun et al 2020;Gautam et al 2020;Kazi Abdul and Khandaker Mursheda, 2020) among the mass, our study was conducted during the 1st phase of the vaccination program in India. The results, presented in this work are based on the response, collected from a sample of 358 online voluntary participants from different states and union territories of India.…”
Section: Introductionmentioning
confidence: 99%
“…The study shows that the majority (86.3%) of the participants were ready to get the vaccination in India. 6 A global survey conducted to identify the potential acceptance of a COVID-19 vaccine also reveals that the majority of the participants were ready to take the vaccine. 6 However, the study also showed that the accelerated pace of development of vaccines heightened the anxiety in public and may affect the acceptance.…”
Section: Introductionmentioning
confidence: 99%